Swimming Critical Velocity Physiological Meaning is Affected by Testing Distances - Ricardo J. Fernandes (International Physiology Journal, 2018)
Swimming is a human activity that relies heavily on individual physiological capabilities. In fact, the swimming general performance equation, proposed several years ago by di Prampero 1, highlighted the energy expenditure, the propulsive efficiency and the hydrodynamic drag as its main determinants. Therefore, coaches and exercise physiologists have been proposing a number of testing protocols aiming to diagnose the swimmers physiological training status. However, most of these protocols are invasive, time consuming and costly (e.g. the oxygen uptake assessment and the blood lactate concentrations determination). In addition, some of these tests have some constraints, as the use of a cumbersome breathing valve for respiratory data collection (cf. 2) and the selection of an averaged value of blood lactate concentrations as an non individualized index of endurance performance 34.
Keywords: swimming